Investigating protein diffusivities in diluted hyaluronic acid solutions using dynamic light scattering - Lou, Hao; Hageman, Michael J (Analytical methods, 2022)
This study aimed to investigate the diffusivities of lysozyme (LYS), ovalbumin (OVA), and hyaluronic acid (HA) in buffered solvents using dynamic light scattering (DLS). For protein/solvent and HA/solvent binary systems, the diffusion coefficients of protein or HA were obtained from autocorrelation function (ACF) curve fitting. Whereas, for protein/HA/solvent ternary systems, the two eigenvalues of the mutual diffusion coefficient matrix were obtained from ACF curve fitting. The results of binary systems showed that at low ionic strength, the diffusion coefficients of protein and HA increased linearly with concentration; at high ionic strength, the diffusion coefficients of OVA and LYS were independent on protein concentration; for HA, the positive linear relationship between diffusion coefficient and concentration existed at high and low ionic strengths, but the slope at high ionic strength was smaller compared to that at low ionic strength. For OVA/HA/solvent ternary systems, the sum of two eigenvalues ( D 1 DLS + D 2 DLS ) was slightly smaller compared to ( D OVA + D HA ), where D OVA and D HA were the diffusion coefficients in their binary systems. On the contrary, for LYS/HA/solvent ternary systems, ( D 1 DLS + D 2 DLS ) were significantly smaller than ( D LYS + D HA ) and the diffusion coefficients in binary and ternary systems exhibited an opposite trend with respect to ionic strength change. The DLS and MD simulation results indicated strong attractive intermolecular interaction existed between LYS and HA molecules, especially at low ionic strength. By using DLS, it was possible to characterize the diffusion coefficients of diluted protein/HA binary and ternary systems. A method based on analyzing the autocorrelation function of the dynamic light scattering is developed to investigate protein diffusivities in diluted protein/solvent binary systems and diluted protein/hyaluronic acid/solvent ternary systems.